Entrepreneurship in Hospitality and The Hotels in The Social Lifestyle of Residents - Nuno Abranja; Bonifácio Rodrigues; Ana Pedroso Lima (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Despite increased scientific attention to tourism and hospitality entrepreneurship themes, there is still a general clearance of the inhabitants in relation to the hotels of their residence region, in terms of social frequency and lifestyle, caused by the fact that hotel strategies are designed only for their guests and very little for local residents. At a time when new tourism markets gain importance never felt before, this paper seeks to provide a new and in-depth understanding through a set of interviews conducted with 35 hotel professionals related to the frequency and type of consumption made by residents of the region in their hotels, as well as the entrepreneurial capacity that these companies have to get closer to local residents by creating innovative products or services more appropriate to this market segment needs, to integrate hotels more into the social lifestyle of locals residents.